Effects of Adriamycin-Cytoxan chemotherapy on hematological and electrolyte parameters among breast cancer patients - Tadesse, Fikremariam Abiye; Leminie, Abebaye Aragaw (Frontiers in Oncology, 2023)
Background Adriamycin-Cytoxan (AC) is a common chemotherapy treatment for breast cancer (BC) patients. Its electrolyte and hematological adverse effects have not been addressed adequately. Objective This study aimed to assess the effect of AC on hematological and electrolyte parameters among BC patients. Methods A hospital-based comparative cross-sectional study design was conducted from March to November 2022. Randomly selected AC-treated (n=100) and untreated (n=100) patients were included. Structured questionnaire and medical records were used to collect sociodemographic data. Anthropometric parameters, hematological indices, and serum electrolytes were measured. Cobas Integra 400+and SYSMEX-XT-4000i were used to analyze serum electrolytes and hematological indices respectively. The data were analyzed using SPSS version 25. Independent t-test and chi-square test were used. p-value <0.05 was considered statistically significant. Results AC-treated patients’ mean total white blood cell (TWBC), neutrophil (NE), lymphocyte (LY), red blood cell (RBC), hemoglobin (Hgb), hematocrit (HCT), and sodium(Na+) values were significantly reduced (p<0.05) than patients with no treatment. However, mean eosinophils (EO), platelet (PLT) counts, red cell distribution-width (RDW), potassium (K+), and plateletcrit (PCT values were significantly increased (p<0.05). Conclusion The majority of blood cells and serum sodium were affected by AC treatment. Incorporating these parameters in the routine analysis and further studies on the detailed mechanism of action of this drug is required.